A Comparative Study of the Perception of Meta-Skills of Higher Education Students in Yala Province - Issara, Nattaluck; Botphiboon, Uchuphorn; Polyiam, Kultida; Dudsdeemaytha, Jitra; Saleemad, Khanittha (Saengtham College Journal, 2025)
This research aimed to study the meta-skills of higher education students in Yala Province and compare the meta-skills perception of higher education students in Yala Province with different personal data. The study was conducted with a sample group of 107 higher education students in Yala Province. The research instrument was a meta-skills analysis measure based on the perception of higher education students in Yala Province. It was found that the meta-skills perceived by higher education students in Yala Province were at a high level overall, 79.60 percent. When considering each sub-skill, it was found that the highest perception of higher education students in Yala Province was Creative problem-solving at 83.40 percent, followed by Resilience at 78.80 percent, and the lowest was Self-awareness. (Self-Awareness) 73.80 percent and when comparing the perception of meta skills of higher education students in Yala Province with different personal information, it was found that 1) different genders have different meta skills perceptions with statistical significance at the 0.05 level, 2) different grade point averages (GPAs) have no statistically significant differences in the perception of meta skills of higher education students in Yala Province at the 0.05 level, and 3) different universities have no statistically significant differences in the perception of meta skills at the 0.05 level.